Trust the man - Crudup, Billy, 1968-; Duchovny, David; Moore, Julianne; Gyllenhaal, Maggie, 1977-; Mendes, Eva, 1974-; LeGros, James; Kimmel, Sidney; Freundlich, Bart, 1970-; Perell, Tim.; Fox Searchlight Pictures; Sidney Kimmel Entertainment (Firm); Process Productions (Firm) (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2006)
Overachieving actress, Rebecca must come to grips with her failing marriage to stay-at-home dad, Tom. While Rebecca's slacker brother, Tobey, can't seem to committ to his aspiring-novelist girlfriend. From the cover.
English track: Dolby digital 5.1.
Special features: audio commentary by writer/director Bart Freundlich and actor David Duchovny; 'Real love : the making of trust the man' featurette; deleted scenes with optional audio commentary by Bart Freundlich and David Duchovny.
Director of photography, Tim Orr ; editor, John Gilroy ; music, Clint Mansell ; costume designer, Michael Clancy ; production designer, Kevin Thompson.
Billy Crudup, David Duchovny, Julianne Moore, Maggie Gyllenhaal, Eva Mendes, James Le Gros.
MPAA rating: R; for language and sexual content.
DVD.
Keywords: Married people -- New York (State) -- New York -- Drama; Marital psychotherapy -- New York (State) -- New York -- Drama; Man-woman relationships -- New York (State) -- New York -- Drama; Men -- Sexual behavior -- New York (State) -- New York -- Drama; Women -- Sexual behavior -- New York (State) -- New York -- Drama; Films for the hearing impaired; Feature films; Comedy films